The relationship of knowledge level, motivation with breast self -examination behaviour in nuns of the Indonesian community province - Rahmat, Alfiana; Purwarini, Justina (International Journal of Research in Medical Sciences, 2023)
Background: Breast self-examination (BSE) is one of the early detection methods for breast cancer that is simple, inexpensive, effective, and non-invasive, although it is not commonly known or used routinely. The primary issues with BSE are a lack of information, a lack of drive, and irregular BSE practices. This causes breast cancer patients to seek treatment at a more advanced stage, making treatment more challenging. This research aims to evaluate the relationship between Indonesian community nuns’ knowledge, motivation, and BSE behaviour. Methods: This research is descriptively correlative and employs a cross-sectional approach. Indonesian community nuns between the ages of 20 and 60 made up the research’s total sampling of 106 respondents. In this research, a questionnaire and chi-square tests were utilized as instruments. If the p value is 0.05, statistical test results are deemed significant. Results: The univariate analysis indicated that 61.3% of respondents had adequate BSE knowledge, 50.9% of respondents were highly motivated, and 50.9% of respondents displayed appropriate behaviour. The results of the bivariate test revealed a correlation between knowledge and BSE-related behaviour (p-value = 0.007) and between motivation and BSE-related behaviour among Indonesian community nuns (p-value = 0.020 and OR = 2.720). Conclusions: On the basis of the research authors’ findings, the regularity of monthly BSE behaviour among Indonesian community nuns must be enhanced and trained continually to develop excellent habits. Through frequent seminars and counselling, the community is expected to equip nuns with an activity program for breast cancer detection.